Culturemes and non-equivalent lexis in dictionaries - Ganoshenko, Y.; Ганошенко, Юрій Анатолійович (Instytut Slawistyki Polskiej Akademii Nauk, 2015)
The article raises the question of the need to improve the structural diversity and operational capabilities of the modern dictionary (bi- or multilingual) to avoid lacunes in the transmission of culturemes and non-equivalent words into another language. Without it the dictionary is incomplete and languages are unequal. The article deals with various options of asymmetry reflection of the culturemes in the context of social and ethno-psychic reality of a native-speaking community. The specifics of lexicographical transmission is observed in order to emphasize the need of further investigation of the linguistic map of the world.
Keywords: cultureme; non-equivalent vocabulary; lacune; asymmetry; dictionary entry